FASN thioesterase domain mutation and fatty acid profile in Holstein Friesian intramuscular fat - D. Cancino-Baier; D. Cancino-Baier; E. Muñoz-Acuña; E. Muñoz-Acuña; J. Quiñones; R. Diaz; J. F. Beltrán; J. Farías; K. Inostroza; R. Huaiquipan; J. B. Sterman Ferraz; N. Sepúlveda (Archives Animal Breeding)
A mutation in the thioesterase domain of the FASN enzyme is associated with a lower percentage of myristic acid when the mutated allele is present, although the underlying mechanism remains unclear. The objective of this study was to evaluate, through in silico simulation, the effect of this mutation on the affinity of the catalytic site of the thioesterase domain for two of its ligands, myristoyl and palmitoyl, and its impact on the fatty acid profile of intramuscular fat. Animals were genotyped using PCR–RFLP, and fatty acid composition was assessed by gas chromatography. Simulations were conducted using the Bos taurus reference sequences (Q71SP7) from the UniProt database. Tertiary structures were generated through homology modeling using PHYRE2. The resulting models were refined with GalaxyRefine and evaluated by generating Ramachandran plots in SWISS-MODEL. Molecular docking was performed with AutoDock Vina. Four molecular dockings were conducted between both enzyme models, wildtype and mutated, and the ligands, resulting in the following combinations: wildtype/palmitoyl, mutated/palmitoyl, wildtype/myristoyl, and mutated/myristoyl. The interaction regions of the generated dockings were visualized using PyMOL software. A decrease in the percentage of myristic and palmitic fatty acids was observed in homozygous individuals with the mutated allele. The mutated/myristoyl complex showed a higher interaction compared to the wildtype/myristoyl complex. However, despite the increased affinity between the mutated enzyme and myristoyl, the possible alteration in the enzyme's structure is likely more relevant in affecting the fatty acid profile of intramuscular fat.